A high-quality chromosome-level genome assembly of Pelteobagrus vachelli provides insights into its environmental adaptation and population history - Li, Jie; Wang, Tao; Liu, Wei; Yin, Danqing; Lai, Zhengqing; Zhang, Guosong; Zhang, Kai; Ji, Jie; Yin, Shaowu (Frontiers in Genetics, 2022)
Pelteobagrus vachelli is a freshwater fish with high economic value, but the lack of genome resources has severely restricted its industrial development and population conservation. Here, we constructed the first chromosome-level genome assembly of P. vachelli with a total length of approximately 662.13 Mb and a contig N50 was 14.02 Mb, and scaffolds covering 99.79% of the assembly were anchored to 26 chromosomes. Combining the comparative genome results and transcriptome data under environmental stress (high temperature, hypoxia and Edwardsiella. ictaluri infection), the MAPK signaling pathway, PI3K-Akt signaling pathway and apelin signaling pathway play an important role in environmental adaptation of P. vachelli, and these pathways were interconnected by the ErbB family and involved in cell proliferation, differentiation and apoptosis. Population evolution analysis showed that artificial interventions have affected wild populations of P. vachelli. This study provides a useful genomic information for the genetic breeding of P. vachelli, as well as references for further studies on fish biology and evolution.